Food insecurity is associated with multiple psychological and behavioural problems among adolescents in five Caribbean countries. Issue 2 (7th February 2023) - Pengpid, Supa; Peltzer, Karl
ABSTRACT: The study aimed to assess associations between food insecurity and multiple psychological and behavioural problems among adolescents in five Caribbean countries. Data from national and cross-sectional school health surveys from 9, 956 adolescents (15 years, median age) in Trinidad and Tobago, Suriname, Jamaica, Anguilla and the Dominican Republic in 2016–2017 were analyzed in 2016–2017. Results show that the prevalence of moderate (rarely or sometimes) past-month food insecurity was 35.9% and severe (mostly or always) food insecurity was 4.6%. Severe food insecurity among adolescents ranged from 2.9% in Dominican Republic to 11.2% in Suriname. In adjusted logistic regression analyses, the higher severity of food insecurity was associated with negative psychological outcomes (loneliness, suicidal ideation, suicide plan, suicide attempt, anxiety, current tobacco use and any trouble from alcohol use) and negative behavioural outcomes (truancy, bullied, physically attacked, physical injury, and multiple sexual partners). Two out of five adolescents experienced some form of food security. Food interventions, such as school feeding programmes, are warranted to reduce negative psychosocial outcomes.